Thophic State of Perupuk Lake based on Phytoplankton in Kampung Pinang Village Kampar District Riau Province - Sibuea, Renny; H Simarmata, Asmika; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMany activities in the Perupuk Lake contribute the input of organic and anorganic mattet that affects the nutrient concentration and increasing thr growth of phytoplankton. A research about Thophic State of Perupuk Lake by Phytoplankton in Kampung Pinang Village Kampar District Riau Province has been conducted in June-July 2019. The location of the water samples to measure water quality defined 3 stations, namely in the inlet, the curve of the lake, and in the end of the lake. In each station, there were 2 sampling points, namely in the surface (0.15 m) and 2 Secchi depth (0.90 m). Samplings were conducted 3 times at intervals of a week. Water quality parameters measured in this research were temperature, transparency, depth, pH, dissolved oxygen, CO2, nitrate and phosphate. Results shown that there were 38 species of phytoplankton that were belonged to 7 classes, namely Chlorophyceae (16 spesies), Bacillariophyceae (4 spesies), Cyanophyceae (5 spesies), Euglenophyceae (1 spesies), Trebouxiophyceae (4 spesies), Cryptophyceae (1 spesies) dan Zygnematophyceae (7 spesies). The phytoplankton abundance of the Perupuk Lake was 46.481-74.959 cells/L. The most common type of phytoplankton present was Monoraphodium griffithii. Results shown that the temperaturewas 28-30 0C, transparency was 40-54 cm, depth was 1-2 m, pH was 5, dissolved oxygen was 5.02-6.81 mg/L, CO2 was 5.99-15.98 mg/L, nitrate was 0.0125-0.9646 mg/L and phosphate was 0.0553-0.2235mg/L and. Based on the type and abundance of phytoplankton present, it can be concluded that the Perupuk Lake can be categorized as mesotrophic.Keywords : Oxbow Lake, Phytoplankton, Water Quality, Monoraphodium griffithii, Mesotrophic